Electron affinity of modified benzene. Issue 4 (28th September 2017) - Driver, Nicholas; Jena, Purusottam
Abstract: The electron affinities of organic molecules obeying Hückel's rule of aromaticity are vanishingly small, if not negative. For example, benzene, a classic example of an aromatic molecule, has an electron affinity of −1.15 eV. Using density functional theory, we have systematically calculated the electron affinities and vertical detachment energies of C6 H6 by substituting H with halogen (F) and superhalogen (BO2 ) moieties, as well as replacing one of the C atoms with B. The ground state geometries were obtained by examining about 330 isomers. The electron affinities are found to steadily increase with these substitutions/replacements, even surpassing that of Cl, the element with the highest electron affinity in the periodic table, in the case of C5 BH(BO2 )5 . In some special cases such as C6 H5 (BO2 ) the electron affinity and vertical detachment energy differ by as much as 5 eV, indicating substantial changes in the geometry as the electron is removed from the anion. We hope that the ability to change the negative electron affinity of C6 H6 to large positive values by substituting H and/or replacing C atom will motivate experimental studies. Abstract : Superhalogens are materials of increasing interest thanks their potential use in novel designs of Li‐Ion batteries. Using density functional theory, the electron affinities and vertical detachment energies of numerous modified benzene molecules, including C6 F6 and C6 (BO2 )6, are calculated. To further increase electron affinity of this molecules, Huckel's Rule for aromaticity has been employed, yielding an organic, aromatic superhalogen molecule: BC5 H(BO2 )5 .